2001
DOI: 10.1046/j.1365-8711.2001.04642.x
|View full text |Cite
|
Sign up to set email alerts
|

The BL Lac heart of Centaurus A

Abstract: A B S T R A C TWe have observed emission from the nucleus of the closest radio galaxy, Centaurus A, from the radio to the gamma-ray band. We construct, for the first time, its overall spectral energy distribution (SED) which appears to be intriguingly similar to those of blazars, showing two broad peaks located in the far-infrared band and at ,0.1 MeV respectively. The whole nuclear emission of Centaurus A is successfully reproduced with a synchrotron self-Compton model. The estimated physical parameters of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
695
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 429 publications
(766 citation statements)
references
References 28 publications
69
695
1
1
Order By: Relevance
“…These correlations support the argument of Chiaberge, Capetti, & Celotti (1999), that the CCC radiation is of a non-thermal synchrotron origin, which is relativistically beamed along with the radio emission. We used the CCC data of 27 3CR FR Is in Chiaberge et al 1999;NGC 7052 and NGC 6251 in Capetti & Celotti (1999) and Hardcastle & Worrall (2000), respectively; 26 3CR FR lIs in Chiaberge, Capetti & Celotti (2000) and BL Lacs in . The Rj values come from the VLBI observations of Giovannini et al 1999 and references therein.…”
supporting
confidence: 85%
“…These correlations support the argument of Chiaberge, Capetti, & Celotti (1999), that the CCC radiation is of a non-thermal synchrotron origin, which is relativistically beamed along with the radio emission. We used the CCC data of 27 3CR FR Is in Chiaberge et al 1999;NGC 7052 and NGC 6251 in Capetti & Celotti (1999) and Hardcastle & Worrall (2000), respectively; 26 3CR FR lIs in Chiaberge, Capetti & Celotti (2000) and BL Lacs in . The Rj values come from the VLBI observations of Giovannini et al 1999 and references therein.…”
supporting
confidence: 85%
“…We recall here that the existence of the postulated structure in BL Lac jets (and FRI radiogalaxies) is supported by a variety of observational and phenomenological arguments (e.g. Chiaberge et al 2000, Giroletti et al 2004, Piner & Edwards 2014, Nagai et al 2014) and also by numerical simulations (e.g. Rossi et al 2008).…”
Section: Discussionmentioning
confidence: 78%
“…The study of obscuration toward the central regions of these galaxies (see e.g. Chiaberge et al 1999;Chiaberge et al 2002;Worrall et al 2003;Balmaverde et al 2006) has shown that the nuclear disks in these galaxies are geometrically and optically thin. This suggests that the standard pc-scale geometrically thick torus is not present in these low-luminosity radio galaxies.…”
Section: Hi 21-cm Absorption In Low-luminosity Radio Galaxiesmentioning
confidence: 99%